Influence of growth intensity of black and white dairy cattle on their reproduction and productivity under free housing - O. Y. Admin; N. G. Admina; А. P. Paliy; R. V. Petrov; L. V. Nagorna; L. M. Kovalenko; S. M. Nazarenko; V. V. Sevastianov (Regulatory Mechanisms in Biosystems, 2024)
Targeted and economically justified livestock breeding, considering the biological characteristics of growing animals, is a key issue in dairy farming. One of the insufficiently studied aspects of livestock breeding is the period of animal development from the first insemination to the first lactation, which affects their safety, productivity, and reproductive capacity. The study was conducted at the breeding station of the Ukrainian black-and-white dairy breed of the state enterprise "Kutuzivka" in Kharkiv district, Kharkiv region, Ukraine. Animals born in different years differed in growth intensity, reproductive performance, and productivity. At the same time, there was a tendency for the milk yield of first-born heifers to improve with an increase in live weight gain from insemination to the first lactation. According to the results of the correlation analysis, this weight gain had a significant relationship with age and live weight at first insemination, milk yield for 90 days, milk yield for 150 days, milk yield for 305 days of lactation, and live weight at first lactation. The survival rate of all first-born heifers with a weight gain of more than 146 kg was 16–21% higher compared to animals with a lower weight gain. Also, such animals had the highest milk yields for all lactation periods. Their advantage in milk yield was 234 kg for the first 90 days of lactation, 331–381 kg for 150 days of lactation, and 573–675 kg for 305 days of lactation. Groups of animals with different live weight gain after the first insemination also had significant differences in the duration of the service period and the number of stillborn calves. The results of the study concluded that the animals with the highest gain were significantly younger and had a higher live weight at insemination as well as the highest live weight in the first lactation. The early maturation of replacement heifers will contribute to the intensive reproduction of the herd, which will increase the profitability of the dairy industry. Further research is needed to determine the effect of growth intensity on the reproductive performance of second and subsequent lactation cows and calf safety.